Performance of Analog Network Coded Communication with Channel Noise Assisted Gain - Ghanti, Basanti; R Patil, Rajendra (International Journal of Engineering and Technology, 2018)
Packet forwarding by embracing interference has created a new insight in the way the interference was understood which we call it as constructive interference. In the present study the performance of Analog Network Coded Communication (ANC) based on the relay gain calculation using Channel Assisted (CA) and Channel noise Assisted (CNA) method is studied and results indicate that in the low Signal to noise ratio (SNR) and high SNR the CNA gives good performance compared to CA in terms of Sum-BER.Â Â